Performance of Finisher Broilers Fed Wet Mash with or Without Drinking Water During Wet Season in the Tropics - Awojobi, H.A.; Oluwole, B.O.; Adekunmisi, A.A.; Buraimo, R.A. (International Journal of Poultry Science, 2009)
Finisher broilers were fed conventional dry and wet mash with varying amounts of water addition (1.0, 1.5, 2.0 parts of water to 1 part of feed) with and without drinking water. Feed intake was higher (P